2018
DOI: 10.1128/jcm.01329-17
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Accelerate PhenoTest BC Kit for Rapid Identification and Phenotypic Antimicrobial Susceptibility Testing Using Morphokinetic Cellular Analysis

Abstract: We describe results from a multicenter study evaluating the Accelerate Pheno system, a first of its kind diagnostic system that rapidly identifies common bloodstream pathogens from positive blood cultures within 90 min and determines bacterial phenotypic antimicrobial susceptibility testing (AST) results within ∼7 h. A combination of fresh clinical and seeded blood cultures were tested, and results from the Accelerate Pheno system were compared to Vitek 2 results for identification (ID) and broth microdilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(81 citation statements)
references
References 69 publications
(82 reference statements)
3
76
0
Order By: Relevance
“…A recent study established an overall sensitivity and specificity for yeasts of 83.3% and 98.4%, respectively (8). The overall essential agreement and the overall category agreement in our study concurs with the multicentre study of Pancholi and colleagues which reported values of 97% (9). The AST for piperacillin-tazobactam and P. aeruginosa has also been optimized in the latest version of the software (5).…”
Section: Discussionsupporting
confidence: 89%
“…A recent study established an overall sensitivity and specificity for yeasts of 83.3% and 98.4%, respectively (8). The overall essential agreement and the overall category agreement in our study concurs with the multicentre study of Pancholi and colleagues which reported values of 97% (9). The AST for piperacillin-tazobactam and P. aeruginosa has also been optimized in the latest version of the software (5).…”
Section: Discussionsupporting
confidence: 89%
“…Since the time to susceptibilities appears to be highly important in antimicrobial stewardship, further research and development of accurate and rapid prediction of susceptibilities may provide the most impactful information sooner. One example of this type of technology, the Accelerate Pheno test, was recently cleared by the Food and Drug Administration [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the time to susceptibilities appears to be highly important in antimicrobial stewardship, further research and development into accurate and rapid prediction of susceptibilities may provide the most impactful information sooner. One example of this type of technology, the Accelerate Pheno test, was recently cleared by FDA and evaluated by a large group (14).…”
Section: Discussionmentioning
confidence: 99%